The Persian version of Penn Parkinson's Daily Activities Questionnaire-15: Face and Content Validity - Nikbakht, Neger; Rezaee, Mehdi; Kalantari, Minoo; Tabatabaee, Seyed Mehdi (Journal of Clinical Physiotherapy Research, 2018)
Introduction: Cognitive deficits impact the ability to perform instrumental activities of daily living (IADL) in patients diagnosed with Parkinson's disease (PD). Improved IADL measurement plays an important role in the assessment of functional independence and new cognition-enhancing treatments in PD. The purpose of this study was to translate and investigate the face and content validity of Penn Parkinson's Daily Activities Questionnaire-15 in Persian. Materials and Methods: This was a methodological study where the forward-backward method was used for the translation process. Face validity by 15 knowledgeable informants (KI) of PD participants and content validity by 15 occupational therapists were evaluated. Face validity was measured using quantitative and qualitative approaches, and quantitative content validity was determined by calculating Content Validity Ratio (CVR) and Content Validity Index (CVI). Results: Face validity was high (2/92-5), and all items were reported to be acceptable and understandable by KI, except for one question that needed to be explained to them with an example. Final corrections were done. Also, CVR (0.73-1) and CVI (0.86-1) were found to be within the acceptable range. Discussion: The Persian version of PDAQ-15 shows strong psychometric properties and also appears suitable for use as a clinical and research tool to evaluate daily cognitive functioning in PD patients. Key words: Parkinson's disease, instrumental activities of daily living, cognition, face validity, content validity